Effect of Different Knee Braces in ACL-Deficient Patients - Focke, Anne; Steingrebe, Hannah; Möhler, Felix; Ringhof, Steffen; Sell, Stefan; Potthast, Wolfgang; Stein, Thorsten (Frontiers in Bioengineering and Biotechnology, 2020)
Knee braces are often used during rehabilitation after ACL injury. There are two main concepts, rigid and soft braces, but studies comparing the two show conflicting results. Most studies used movement tasks with low translational or rotational loads and did not provide joint kinematics. Therefore, the purpose of this study was to investigate the influence of two different knee braces (rigid vs. soft) on knee joint kinematics in ACL-deficient patients compared to an unbraced control condition using two tasks (walking and 180° cutting) provoking knee movements in the frontal and transverse planes. 17 subjects with ACL-deficient knees participated in this study. 3D knee joint kinematics were recorded. To provoke frontal plane knee joint motion a laterally tilting plate was applied during a walking task. Both braces reduced the maximum valgus angle compared to the unbraced condition, stabilizing the knee joint against excessive valgus motion. Yet, no differences in peak abduction angle between the two braces were found. However, a significant extension deficit was observed with the rigid brace. Moreover, both braces increased transverse plane RoM and peak internal rotation angle, with the effects being significantly larger with the rigid brace. These effects have been associated with decreased knee stability and unphysiological cartilage loading. Therefore, the soft brace seems to be able to limit peak abduction with a lesser impact on physiological gait compared to the rigid brace. The cutting task was selected to provoke transverse plane knee movement and large external knee rotation was expected. However, none of the braces was able to reduce peak external knee rotation. Again, an increase in transverse plane RoM was observed with both braces. Based on these results, no brace outmatched the other in the second task. This study was the first attempt to clarify the effect of brace design for the stabilization of the knee joint during movements with frontal and transverse plane loading. However, to provide physicians and patients with a comprehensive guideline for brace usage, future studies will have to extent these findings to other daily or sportive movement tasks.